1980
DOI: 10.1159/000225401
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Prolactin and Androgens in Patients with Prostatic Diseases

Abstract: Testosterone (T), dihydrotestosterone (DHT) and prolactin (HPr) levels were determined in normal males and females, in patients with benign prostatic hypertrophy (BPH) and in clinically stable patients with prostatic carcinoma (CAP), intact and orchiectomized. CAP patients were either untreated or on different modalities of therapy. The HPr levels were higher in prostatic cancer patients, in BPH patients, and in subjects on estrogen therapy. No significant differences were found between controls or patients tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 25 publications
2
12
0
1
Order By: Relevance
“…In this respect, the PRLR gene (chromosome 5p13.2) is located in a region that was found to show high genomic instability in prostate tumor tissues: amplification of the 5p13.1-p13.3 locus was indeed significantly associated with a negative outcome [75]. This is in agreement with a former study that identified a prostate cancer susceptibility locus at 5p13-q11 by linkage analysis [70]. Strikingly, the 5p13.1-p13.3 locus contains several genes that are relevant to prostate cancer, including the prostate cancer biomarker alpha-methylacyl-CoA-racemase (AMACR) [10], mTOR signaling (RICTOR), S-phase Kinase-associated Protein 2 (SKP2) and two genes whose products trigger the STAT5 pathway: interleukin-7 receptor (IL7R) and the PRLR.…”
Section: Prlr Levelssupporting
confidence: 90%
“…In this respect, the PRLR gene (chromosome 5p13.2) is located in a region that was found to show high genomic instability in prostate tumor tissues: amplification of the 5p13.1-p13.3 locus was indeed significantly associated with a negative outcome [75]. This is in agreement with a former study that identified a prostate cancer susceptibility locus at 5p13-q11 by linkage analysis [70]. Strikingly, the 5p13.1-p13.3 locus contains several genes that are relevant to prostate cancer, including the prostate cancer biomarker alpha-methylacyl-CoA-racemase (AMACR) [10], mTOR signaling (RICTOR), S-phase Kinase-associated Protein 2 (SKP2) and two genes whose products trigger the STAT5 pathway: interleukin-7 receptor (IL7R) and the PRLR.…”
Section: Prlr Levelssupporting
confidence: 90%
“…In contrast to several previous studies (Harper et al, 1976;Bartsch et al, 1977b;Hammond et al, 1978;Habib, 1980;Saroff et al, 1980;H0isaeter et al, 1982;Zumoff et al, 1982;Ranikko & Adlercreutz, 1983;Hulka et al, 1987), the control group was population-based and prostate cancer was ruled out by digital rectal examination and serum analysis for prostate-specific antigen. Serum samples were drawn, stored and analysed according to highly standar- dised routines.…”
Section: Discussionmentioning
confidence: 96%
“…In two instances, steroid hormone levels were analysed in serum samples stored for a number of years before the disease was manifested, using a nested case-control design (Nomura et al, 1988;Barrett-Connor et al, 1990). In general, however, serum samples were drawn at the time of diagnosis of the cases (Harper et al, 1976;Bartsch et al, 1977a;Bartsch et al, 1977b;Hammond et al, 1978;Ghanadian et al, 1979;Habib, 1980;Jackson et al, 1980;Saroff et al, 1980;Ahluwalia et al, 1981;Drafta et al, 1982;Hill et al, 1982;H0isaeter et al, 1982;Meikle & Stanish, 1982;Zumoff et al, 1982;Ranikko & Adlercreutz, 1983;Meikle et al, 1985;Hulka et al, 1987;Hsing & Comstock, 1989). In general such comparisons have given conflicting results.…”
mentioning
confidence: 99%
“…Circulating PRL levels increase with age, and its concentration is therefore high when these pathologies develop [38,39]. However, conflicting results have been reported, showing either an increase in PRL levels [40,41], or unchanged levels of this hormone in the case of benign prostatic hyperplasia (BPH), but increased levels in patients with prostatic carcinoma [42]. These differences could be partially explained by the recent observation that PRL is produced in the prostate itself [43,44].…”
Section: Prolactinmentioning
confidence: 99%